Effects of heavy metals and nitroaromatic compounds on horseradish glutathione S-transferase and peroxidase - Nepovím, Ales; Podlipná, Radka; Soudek, Petr; Schröder, Peter; Vanek, Tomás (Chemosphere, 2004)
Glutathione S-transferase (GST) and peroxidase (POX) activities have a direct relation to the effect of stress on plant metabolism. Changes in the activities of the enzymes were therefore studied. Horseradish hairy roots were treated by selected bivalent ions of heavy metals (HMs) and nitroaromatic compounds (NACs). We have shown differences in GST activity when assayed with substrates 1-chloro-2,4-dinitrobenzene (CDNB) and 1,2-dichloro-4-nitrobenzene (DCNB). The conjugation of DCNB catalysed by GST was inhibited in all roots treated with HMs as compared to non-treated roots, whereas NACs caused induction of the activity in dependence on the exposition time and concentration of compounds. The conjugation of CDNB by GST was not affected to the same extent. The increase of GST activity was determined in cultures treated by nickel (0.1 mM) and diaminonitrotoluenes (DANTs, 0.1 mM) for 6 h, whereas the roots treated by 2,4,6-trinitrotoluene (TNT), 4-amino-2,6-dinitrotoluene (ADNT) and dinitrotoluene (DNT, 1.0 mM) needed 27 h treatment to induce the activity. The POX activity of cultures treated by HMs was inhibited to 17-35% in comparison to non-treated cultures. The POX activity of roots treated by TNT (0.1 and 1.0 mM) for 6 and 27 h and by ADNT (0.1 and 1.0 mM) for 6 h was inhibited. A partial increase of POX activity was measured in roots treated by all NACs for 27 h. The content of oxidized glutathione (GSSG) and reduced glutathione (GSH) in the roots differed significantly. It was followed as a symptom of the stress reaction of the plant metabolism to the effect of NACs and HMs.
Keywords: těžké kovy; Chromatography, High Pressure Liquid; DNA primery; Horseradish Peroxidase; Transformation, Genetic; Glutathione Transferase; vysokoúčinná kapalinová chromatografie; glutathiontransferasa; peroxidasa; Nitrobenzenes; křenová peroxidasa; DNA Primers; Peroxidase; transformace genetická; Armoracia; Metals, Heavy; nitrobenzeny